2017
DOI: 10.1021/acs.inorgchem.7b02421
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Substituent Effects in Manganese Pyridinophane Complexes: Implications for Oxygen-Evolving Catalysis

Abstract: A series of Mn(II) complexes of differently substituted pyridinophane ligands, (PyNR)MnCl (R = Pr, Cy) and [(PyNR)MnF](PF) (R = Pr, Cy,Bu) are synthesized and characterized. The electrochemical properties of these complexes are investigated by cyclic voltammetry, along with those of previously reported (PyNMe)MnCl and the Mn(III) complex [(PyNMe)MnF](PF). The electronic structure of this and other Mn(III) complexes is probed experimentally and theoretically, via high-frequency and -field electron paramagnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 61 publications
4
26
0
Order By: Relevance
“…[3][4][5]7 Congeners of pyclen have been widely studied to tune their properties and reactivity. 8 For example, it was observed that 12and 13-membered cavities cannot accommodate planar coordination compared to 14-membered py-2,3-cyclam, which signicantly affects the electrochemical properties of the complex and leads to the stabilization of rather uncommon metal oxidation states. 9,10 Introduction of pendant arms, amine functionalization on the macrocycle, and differing numbers of coordinating atoms are all examples of other modications that have been studied to tune reactivity of pyridinophanes to achieve changes to geometric rigidity, electrochemical properties, and coordination environments, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5]7 Congeners of pyclen have been widely studied to tune their properties and reactivity. 8 For example, it was observed that 12and 13-membered cavities cannot accommodate planar coordination compared to 14-membered py-2,3-cyclam, which signicantly affects the electrochemical properties of the complex and leads to the stabilization of rather uncommon metal oxidation states. 9,10 Introduction of pendant arms, amine functionalization on the macrocycle, and differing numbers of coordinating atoms are all examples of other modications that have been studied to tune reactivity of pyridinophanes to achieve changes to geometric rigidity, electrochemical properties, and coordination environments, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Metal complexes derived from L2 and modications to the C-C linkers have been extensively explored, as noted above. 8,[25][26][27] The 4-OMe substituted pyridinophane was studied as a precursor to a scaffold used for iron-catalyzed oxidation chemistry. 26 The 4-Br substituted pyridinophane was developed as an intermediate for synthesis of molecules explored for biomedical imaging.…”
Section: Introductionmentioning
confidence: 99%
“…15 High spin manganese(II) and manganese(III) complexes of L-N4R2 (R = Me, iPr and tBu) ligands are known and do not exhibit electronic lability. [16][17][18][19] The L-N4R2 family of ligands display remarkable conformational flexibility in their metal complexes. 20 Clearly, very subtle electronic and steric factors govern the redox states and charge distributions in these metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The TM centers are usually bound by two (the first and the second) concentric coordination spheres. In the first coordination sphere, corrole, porphyrin and pyridinophane containing pyrrole or pyridine rings are the most commonly used ligands. These ligands are directly attached to the high‐valent TM ions, forming stable four‐coordinated TMN 4 units ( Figure a) as water oxidation centers .…”
Section: Smmcs For Water Oxidationmentioning
confidence: 99%